PENENTUAN MODEL KINETIKA DINAMIS PADA ADSORPSI LIMBAH CAIR ZAT WARNA REMAZOL YELLOW FG ARTIFISIAL MENGGUNAKAN KOMPOSIT KARBON AKTIF-KITOSAN - Galuh Arya Ramdani; Zainal Arifin; Muhammad Kasim (JURNAL TEKNIK KIMIA VOKASIONAL (JIMSI), 2021)
Dye waste that contains synthetic dyes like Direct Black 38, Remazol Yellow FG, and Reactive Red 2 in high concentration, is the main source of water pollution which can decrease the quality and ecosystem of water due to its difficult degradation properties. Physical and chemical adsorption method using adsorbent like activated carbon-chitosan composites can be carried out to decrease the concentration of dye waste. The purpose of this research is to find out the adsorption capacity of activated carbon-chitosan composites on Remazol Yellow FG dye waste using fixed bed column continuous system. The composites were made by adding 1:1 of the activated carbon into chitosan solution and then dropping it into the 15% NaOH-96% Ethanol in 4:1 v/v as the coagulant. Then, composites were used to adsorb the dye waste in order to find out the adsorption capacity. Next, samples were analyzed using UV-Vis Spectrophotometer. The results showed the optimum point was on 8 mL/min flow rate. The best adsorpstion capacity of 1.21781 mg/g was obtained in Thomas and Yoon-Nelson’s Models.